Positron annihilation in mordenite zeolite - Trinh, Hoa Lang; Chau, Van Tao; Le, Hoang Lam; Tran, Quoc Dung (Nuclear Science and Technology, 2016)
The theoretical study of the positron annihilation in complex material such as zeolite is greatly significant to support and increase the accuracy analysis of the material structure from the experimental data of the positron annihilation. The mordenite zeolite is a big and complicated structure consisting of channels and cavities. The analysis of the mordenite structure is studied by the PALS so depending on the selection of the positron lifetime components of the positron annihilation spectra fitting methods. Therefore, these positron life times in on TO4, Na, Ca, K, Fe, H2O and the rings which form the channels and cavities are sophisticatedly studied by the DFT calculation using Ab-initio. The mordenite and modified mordenite zeolite structures are precisely analyzed, and the physical behaviors of the positron in these are more understood by these theoretical results.